Black Hawk down [videorecording (DVD)] - Scott, Ridley; Hartnett, Josh, 1978-; McGregor, Ewan, 1971-; Sizemore, Tom, 1961-; Bowden, Mark, 1951- (Columbia TriStar Home Entertainment, 2002)
With exacting detail, the film re-creates the American siege of the Somali city of Mogadishu in October 1993, when a 45-minute mission turned into a 16-hour ordeal of bloody urban warfare. Helicopter-borne U.S. Rangers were assigned to capture key lieutenants of Somali warlord Muhammad Farrah Aidid, but when two Black Hawk choppers were felled by rocket-propelled grenades, the U.S. soldiers were forced to fend for themselves in the battle-torn streets of Mogadishu, attacked from all sides by armed Aidid supporters.